THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE TEACHING - MAXBUBA SULTANOVA SULTANBEKOVNA, (TADQIQOTLAR, 2026)
ABSTRACT   This study examines the role of Artificial Intelligence (AI) in English language teaching  and  learning.  The  rapid  development  of  AI  technologies  has  transformed educational  practices  by  providing  innovative  tools  for  language  instruction, assessment, and personalized learning. AI-powered applications, including intelligent tutoring systems, chatbots, speech recognition software, automated writing evaluation tools, and adaptive learning platforms, enable learners to improve their language skills more efficiently and interactively. The research highlights how AI enhances the teaching of English by supporting vocabulary  acquisition,  grammar  practice,  pronunciation  improvement,  reading comprehension, writing development, and speaking fluency. Furthermore, AI assists teachers in managing classroom activities, monitoring student progress, and providing individualized feedback. The integration of AI into language education contributes to increased learner motivation, engagement, and autonomy.